The Tribes We Lead: Understanding the Antecedents and Consequences of Brand Evangelism Within the Context of Social Communities - Cestare, Toni Ann; Ray, Ipshita (Journal of Marketing Development and Competitiveness, 2019)
Brand evangelism has significant potential to impact loyalty, thereby making the construct an important point of interest for practitioners and researchers alike. This study attempts to augment existing literature by demonstrating how antecedent constructs such as trust and sentiment operate in unique and distinctive ways when mediated by brand evangelism, especially as it relates to two very different outcome variables in attitudinal and behavioral loyalty. While brand evangelism is found to be a mediator for the impact of sentiment on loyalty, it interestingly does not seem to be a mediator for the impact of trust on loyalty.